Inorganic sulfide solid electrolyte and preparation method thereof
By introducing doped elements and mixed halogen into the inorganic sulfide solid electrolyte, the problem of instability of the electrolyte under air conditions is solved, and the high ion conductivity and air stability is achieved, which is suitable for the application of all-solid lithium batteries.
Patent Information
- Application Number
- CN202311024698.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-08-14
AI Technical Summary
The existing inorganic sulfide solid electrolytes are unstable under air conditions, resulting in structural changes and reduced ion conductivity, limiting their application in all-solid lithium batteries.
By performing double-position substitution in the sulfide electrolyte, doping elements such as Sn, Si, Al, Ge, Zr, etc., and using mixed halogen and proportional design, the air stability and ion conductance of the electrolyte are improved.
It realizes that the air stability of the electrolyte is improved while maintaining high ion conductance, meets the use requirements of all-solid-state batteries, and reduces production costs.
Smart Images

Figure CN117199507B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an inorganic sulfide solid electrolyte and a preparation method thereof. Background Art
[0002] Since the commercialization of lithium-ion secondary batteries in the early 1990s, they have developed rapidly due to their advantages such as high energy density and long service life. However, the lithium-ion batteries commonly used at present are liquid-phase batteries, which contain flammable organic electrolytes, and therefore have serious safety hazards. In recent years, the frequent occurrence of safety accidents in liquid-phase lithium-ion power batteries has greatly restricted the further use of this system. The use of non-flammable inorganic solid materials as lithium-ion battery electrolytes can not only eliminate the safety hazards caused by organic electrolyte leakage and thermal runaway inside the battery during battery use, but also can be used under extreme conditions such as high and low temperatures. Further enhance the value of lithium secondary batteries and expand their application areas. Therefore, the research and development of inorganic solid electrolytes with high lithium ion conductivity and high stability is the key to the development of lithium secondary batteries with high safety.
[0003] According to the classification of the types of negative ions in inorganic solid electrolyte materials, oxide solid electrolytes and sulfide solid electrolytes are currently the most studied and have the greatest application potential. Compared with oxide electrolytes, the sulfur ions in sulfide electrolytes have a lower electronegativity and a lower binding force on cations; at the same time, the radius of sulfur ions is larger, which is conducive to the migration of lithium ions. Therefore, the ion conductivity of sulfide electrolytes is higher than that of oxides, and some sulfide electrolytes even have higher room temperature ion conductivity than organic electrolytes. At present, the research on inorganic sulfide electrolytes is mainly focused on Li 2 SP 2 S 5 , Li 2 S-MS x -P 2 S 5 , Li 2 SP 2 S 5 -LiX and other systems.
[0004] However, the inorganic sulfide electrolytes reported so far are not stable under air conditions. This type of sulfide electrolyte undergoes irreversible chemical reactions with oxygen, water vapor, carbon dioxide, etc. in the air atmosphere, resulting in structural changes and reduced ion conductivity, which seriously restricts its application in all-solid-state lithium batteries. In response to this problem, a large number of studies have focused on improving it through the introduction of additives and surface protective layers. The disadvantage of this method is that it reduces the ion conductivity of the sulfide solid electrolyte.
[0005] In view of this, it is necessary to provide a doped modified sulfide solid electrolyte that can maintain high ion conductivity while having high air stability, meet the requirements of large-scale production of all-solid-state batteries, and be suitable for industrial large-scale production. Summary of the invention
[0006] In order to solve the above technical problems of the present invention, the present invention provides an inorganic sulfide solid electrolyte and a preparation method thereof. The electrolyte material performs double substitution on the P and S positions to improve air stability, and improves ion conductivity by mixing halogens and proportion design to meet the use requirements of all-solid-state batteries. The preparation method of the inorganic sulfide solid electrolyte is simple and effective, with low production cost, and has good stability and high lithium ion conductivity, which is expected to solve the practical application problem of inorganic sulfide electrolytes as high-performance all-solid-state lithium secondary battery electrolytes.
[0007] The present invention has found that a sulfide solid electrolyte with higher stability can be obtained by replacing part of the P element with one or more of Sn, Si, Al, Ge, and Zr, and replacing part of the S element with O. At the same time, by adjusting the ratio between the doping amount of the two doping elements and the content of the composite halogen, as well as the composition of the composite halogen, a high ion conductivity can be obtained.
[0008] According to a first aspect of the present invention, the present invention provides an inorganic sulfide solid electrolyte, the general formula of which is shown as follows: Li 7+a-c P 1-a M a S 6-b-c O b X c (I);
[0009] Wherein, M is one or more of Sn, Si, Al, Ge, and Zr; <a≤0.3,0<b<2.0,0.0≤c≤1.8;
[0010] X c Cl i Br j I k , and 0≤i≤1.0, 0≤j≤1.0, 0≤k≤1.0, and i, j, k
[0011] At least two of them are not 0, i+j+k=c.
[0012] The present invention has found that the introduction of one or more heterovalent ions of Sn, Si, Al, Ge, and Zr can enhance the PS in the sulfide solid electrolyte. 4PS bonds in tetrahedrons; coupled with O anions, the stability of free S in sulfide electrolytes is enhanced. The two effects together improve the stability of sulfide solid electrolyte materials. The defect of this doping effect is that it leads to a decrease in ion conductivity. Further regulation of the type and ratio of mixed halogens can effectively change the disorder of S / X in the lattice, reduce the Li ion conduction resistance, and improve the ion conductivity.
[0013] Further, 0.01≤a≤0.15, 0.01≤b<1.0, 0.9≤c≤1.8, 2.5a+0.7<(b+c)<1.5a+1.8.
[0014] In the above scheme, by further defining a, b, c and the relationship among them, the elements in the inorganic sulfide solid electrolyte can achieve better synergistic effect, so as to obtain an inorganic sulfide solid electrolyte with better performance.
[0015] Further, 2.5a+0.7<(b+c)<1.5a+1.7.
[0016] Further, 0.25≤i / (i+j+k)≤0.75.
[0017] Further, 0.32≤i / (i+j+k)≤0.67.
[0018] Because Br - and I - The ionic radius is larger than Cl - Ion radius, so with the increase of Br or I content, the lattice parameter gradually increases, but when the content is too high, it is easy to generate impurities, affecting the material properties. In addition, the appropriate Cl / Br ratio can regulate Cl - The occupancy of Wyckoff 4a and 4d sites, and the anion disorder of Wyckoff 4a / 4d sites directly affect the material performance. Therefore, in the above scheme, by further limiting the proportion of Cl in X, an inorganic sulfide solid electrolyte with better performance can be obtained.
[0019] Furthermore, in the Raman spectrum, at 310-380 cm -1 There are characteristic peaks.
[0020] Furthermore, the inorganic sulfide solid electrolyte is a solid solution phase type inorganic sulfide solid electrolyte material.
[0021] Further research has found that any of the above sulfide solid electrolyte materials, with the increase of the M doping amount in the solid solution phase, the obtained inorganic sulfide solid electrolyte material has better air stability. Furthermore, by adjusting the type and ratio of the halogen element in the solid solution, the ion conductivity of the material can be further adjusted.
[0022] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned inorganic sulfide solid electrolyte, comprising the following steps:
[0023] Step (1): mixing the required raw materials according to a proportion and then grinding them under the protection of an inert atmosphere;
[0024] Step (2): heat treating the ground material.
[0025] Furthermore, in step (1), the grinding is carried out in a ball mill, the grinding linear speed v is 7.5-16.0 m / s, the grinding time t is 10-24 h, and 5.0E+05m≤v×t≤6.0E+05m.
[0026] In the above scheme, by limiting the grinding linear velocity and time within a reasonable range, it is beneficial to improve the grinding efficiency, which is more conducive to preparing an inorganic sulfide solid electrolyte material with high ionic conductivity.
[0027] Furthermore, in step (2), the heat treatment temperature is 400°C-600°C, the heat treatment time is 5-24h, and the protective gas is an inert gas.
[0028] In the above scheme, by limiting the temperature and time of the heat treatment within a reasonable range, it is more conducive to preparing an inorganic sulfide solid electrolyte material with high ionic conductivity.
[0029] According to the third aspect of the present invention, the present invention also provides a lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the solid electrolyte layer contains the above-mentioned inorganic sulfide solid electrolyte, or an inorganic sulfide solid electrolyte prepared by the above-mentioned preparation method.
[0030] The technical solution provided by the present invention has the following beneficial effects:
[0031] The inorganic sulfide solid electrolyte of the present invention adopts one or more of Sn, Si, Al, Ge, and Zr to replace part or all of the P element in the sulfide electrolyte, O to replace part of the S element, and controls the ratio between M and O and the type and ratio of the mixed halogen to form an inorganic sulfide solid electrolyte material with a solid solution phase structure, thereby obtaining a material with higher stability and higher ion conductivity. Compared with the prior art, the present invention provides a new method for improving the air stability and ion conductivity of sulfide based on double element and mixed halogen substitution. The method is simple and effective, and the obtained sulfide electrolyte is stably stored under air conditions without any coating layer or additive protection. This type of material is simple to prepare and has low production cost; at the same time, the obtained inorganic sulfide solid electrolyte material has controllable ion conductivity and has excellent performance when used as an inorganic electrolyte and electrode material additive in an all-solid-state lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 The Raman curves of the solid electrolyte materials obtained in Example 4 and Comparative Example 8 are shown. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] If no specific techniques or conditions are specified in the examples of the present invention, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0036] Example 1
[0037] In the glove box, follow the Li 6.1 P 0.9 Sn 0.1 S 4.9 O 0.1 Cl 0.65Br 0.35 The element ratio in Li 2 S.P. 2 S 5 、SnS 2 , Li 2 O, LiCl and LiBr, place the above raw materials in a 50ml zirconium oxide ball mill, add 50g of 5mm diameter zirconium oxide balls. Place the sealed ball mill on the ball mill, set the speed to 400rpm (linear speed 8.6m / s), and ball mill for 18h. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, from room temperature to 550℃ in 100min, and maintained at this temperature for 8h, then controlled to cool to 50℃ for 4h, and Li 6.1 P 0.9 Sn 0. 1 S 4.9 O 0.1 Cl 0.65 Br 0.35 Solid electrolyte materials.
[0038] Examples 2 to 12, Comparative Examples 1 to 8
[0039] Except for weighing each raw material according to the element ratio in Table 1, other synthesis conditions are the same as those in Example 1. It should be noted that the ball milling time and heat treatment temperature are slightly different depending on the composition.
[0040] Comparative Example 9
[0041] The difference compared with Example 1 is that the sintering temperature is 620°C.
[0042] Comparative Example 10
[0043] The difference compared with Example 1 is that the sintering temperature is 380°C.
[0044] Comparative Example 11
[0045] Compared with Example 1, the difference is that the ball milling time is 30 hours.
[0046] Comparative Example 12
[0047] Compared with Example 1, the difference is that the ball milling time is 8.5h.
[0048] Air stability test of solid electrolyte materials
[0049] The solid electrolyte materials obtained in Examples 1 to 18 and Comparative Examples 1 to 12 were subjected to an air stability test. In a glove box, 300 mg of the solid electrolyte material was weighed and placed in a 5 ml open glass bottle. The glass bottle was then placed in a reaction box with a specific humidity air flow and allowed to stand at room temperature for 24 hours. The relative humidity of the dry air was 10% and the air flow rate was 100 ml / min. After the standing period, the sample was taken out for an ion conductivity test.
[0050] The S / X disorder of Example 3, Example 4, Example 8, Comparative Example 1 and Comparative Example 2 are 46.3%, 49.1%, 50.7%, 61.4% and 21.8%, respectively. It can be seen that the mixed halogen has a very obvious regulating effect on the S / X disorder, and it also reveals that the S / X disorder should be within a certain range, and too large or too small is not conducive to the improvement of ion conductivity.
[0051] Table 1 Composition, ion conductance and stability data of Examples 1 to 18 and Comparative Examples 1 to 12
[0052]
[0053]
[0054] Table 1 is a summary of the composition, ion conductance and stability data of Examples 1 to 18 and Comparative Examples 1 to 12. The experimental results of Examples 1 to 18 show that the inorganic sulfide solid electrolyte provided by the present invention has high ion conductance and good air stability. The material composition is simple, the raw materials are readily available, the preparation method is simple, the production cost is low, the stability is good, and the lithium ion conductivity is high. It is expected to solve the practical application problem of inorganic sulfide electrolytes as high-performance all-solid-state lithium secondary battery electrolytes.
[0055] It can be seen from the results of Example 3 and Comparative Examples 1-2 that the inorganic sulfide solid electrolyte of the present invention can effectively change the disorder of S / X in the lattice, reduce the Li ion conduction resistance, and improve the ionic conductivity by adopting mixed halogens and regulating their corresponding proportions.
[0056] From the comparison results of Example 11 and Comparative Example 3, it can be seen that the inorganic sulfide solid electrolyte of the present invention can enhance the PS in the sulfide solid electrolyte by introducing one or more heterovalent ions of Sn, Si, Al, Ge, and Zr. 4 PS bonds in the tetrahedron; at the same time, coupling with O negative ions also enhances the stability of free S in sulfide electrolytes. These two effects together improve the stability of sulfide solid electrolyte materials.
[0057] From the comparison results of Example 11 and Comparative Example 3, and Example 10 and Comparative Examples 4-5, it can be seen that the inorganic sulfide solid electrolyte of the present invention uses one or more of Sn, Si, Al, Ge, and Zr to replace part or all of the P element in the sulfide electrolyte, O to replace part of the S element, and controls the ratio between M and O and the type and ratio of the mixed halogen to form an inorganic sulfide solid electrolyte material with a solid solution phase structure, thereby obtaining a material with higher stability and higher ion conductivity.
[0058] It can be seen from the comparison between Comparative Examples 6-8 and Examples 1-18 that the inorganic sulfide solid electrolyte material of the present invention can greatly improve the ion conductivity and stability of traditional common sulfide solid electrolyte materials after element doping and combined with preparation process control.
[0059] Figure 1 The Raman spectra of the solid electrolytes prepared in Example 4 and Comparative Example 8 show that the inorganic sulfide solid electrolyte of the present invention has a Raman spectrum of 310-380 cm -1 There are obvious characteristic peaks in the range, corresponding to the vibration of the SM bond, which proves that the M element is doped into the lattice and forms an SM bond, enhancing the stability of the S element and thus improving the stability of the inorganic sulfide solid electrolyte material.
[0060] It can be seen from the comparison results of Example 1 and Comparative Examples 9-12 that in the process of preparing the inorganic sulfide solid electrolyte of the present invention, process parameters such as heat treatment temperature and grinding time are very important. Controlling process parameters such as heat treatment temperature and grinding time within a reasonable range is beneficial to improving the ionic conductivity of the final inorganic sulfide solid electrolyte.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An inorganic sulfide solid electrolyte, characterized in that: Its general formula is shown below: Li 7+a-c P 1-a M a S 6-b-c O b X c (I); Wherein, M is one or more of Sn, Si, Al, Ge, and Zr; 0.01≤a≤0.15, 0.01≤b<1.0, 0.9≤c≤1.8, 2.5a+0.7<(b+c)<1.5a+1.7; X c Cl i Br j I k , and 0≤i≤1.0, 0≤j≤1.0, 0≤k≤1.0, and i, j, k At least two of them are not 0, i+j+k=c; 0.25≤i / (i+j+k)≤0.75; In the Raman spectrum, at 310-380 cm -1 There are characteristic peaks at The preparation method of the inorganic sulfide solid electrolyte comprises the following steps: Step (1): mixing the required raw materials according to a proportion and then grinding them under the protection of an inert atmosphere; Step (2): heat treating the ground material; In step (1), the grinding is carried out in a ball mill, the grinding linear speed v is 7.5-16.0 m / s, the grinding time t is 10-24 h, and 5.0E+05m≤v×t≤6.0E+05m; In step (2), the heat treatment temperature is 400°C-600°C, the heat treatment time is 5-24h, and the protective gas is an inert gas.
2. The inorganic sulfide solid electrolyte according to claim 1, characterized in that 0.32≤i / (i+j+k)≤0.
67.
3. The method for preparing the inorganic sulfide solid electrolyte according to claim 1 or 2, characterized in that: The steps include: Step (1): mixing the required raw materials according to a proportion and then grinding them under the protection of an inert atmosphere; Step (2): heat treating the ground material.
4. The preparation method according to claim 3, characterized in that: In step (1), the grinding is carried out in a ball mill, the grinding linear velocity v is 7.5-16.0 m / s, the grinding time t is 10-24 h, and 5.0E+05m≤v×t≤6.0E+05m.
5. The preparation method according to claim 3, characterized in that: In step (2), the heat treatment temperature is 400°C-600°C, the heat treatment time is 5-24h, and the protective gas is an inert gas.
6. A lithium secondary battery comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, characterized in that: The solid electrolyte layer contains the inorganic sulfide solid electrolyte according to claim 1 or 2, or the inorganic sulfide solid electrolyte prepared by the preparation method according to any one of claims 3-5.
Citation Information
Patent Citations
High-stability inorganic sulfide solid electrolyte and preparation method thereof
CN113363569A
Sulfide solid electrolyte, preparation method thereof and all-solid-state lithium ion battery
CN115579511A
Solid electrolyte and solid-state battery comprising same
CN116325267A